VASYL STEFANYK AND UKRAINIAN RADICAL MOVEMENT IN POKUTTYA (IN THE LATE XIXth – EARLY XXth CENTURIES) - Королько, А. З. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article highlights the role and place of Vasyl Stefanyk in the organization of Ukrainian radical movement in Pokuttya in the late XIXth – early XXth centuries. The peculiarities of the formation of his ideology and social and political views are analyzed. The role of Vasyl Stefanyk in the process of the Radical Party’s organizational formation ші shown. The cooperation of Vasyl Stefanyk with party bodies, involvemend in the election campaigns to the State Council (Austrian Parliament) and Galician Regional Diet, which took place within the region, are observed. The treatment of the member of «Pokuttia Trinity» to the inner party conflict in the late 1890’s is investigated. The main areas of Vasyl Stefanyk’s practice in URP in the early XX century are observed.